Benzene pyrolysis and PM formation study using a flow reactor. (15th October 2018) - Kashiwa, Koki; Kitahara, Takahiro; Arai, Masataka; Kobayashi, Yoshihiro
Abstract: The main component of PM formed in the combustion field is soot, and its formation mechanism is hydrocarbon fuel partial oxidation. Then as the first step of this PM formation research work, benzene pyrolysis and formation of PM in a diluted benzene-oxygen mixture were studied using a flow reactor. Experimental studies were conducted under zero O2 condition and O2 exist condition, respectively, and the influence on benzene pyrolysis and formation of PM due to exist or absence of oxygen was discussed. The effects of temperature and oxygen on PM formation were also discussed by independent control of temperature and oxygen concentration. PM sampled from the flow reactor was dried up to separate volatile compositions from soot. PM composition change by oxygen concentration and temperature were analyzed in detail. As the result, it was found that PM formation behavior at low temperature condition was different from that of high temperature condition. The valley temperature between them was around 1273 K. It decreased with the addition of oxygen. Under low temperature condition, small amount of PM was formed from benzene-N2 mixture without oxygen. It increased with the addition of oxygen. Main composition of this PM was low boiling point SOF. Under high temperature condition, large amount of PM was formed from benzene-N2 mixture without oxygen. It decreased with the addition of oxygen.